Serum Free Light Chain Assay: Shift Toward a Higher κ/λ Ratio. (30th December 2019) - Rindlisbacher, Barbara; Schild, Christof; Egger, Florence; Bacher, Vera U; Pabst, Thomas; Leichtle, Alexander; Andres, Martin; Sédille-Mostafaie, Nazanin
Abstract: Background: The analysis of serum free light chains (FLCs) is clinically relevant for the diagnosis and therapeutic management of clonal plasma cell disorders. This study compares the performance of monoclonal and polyclonal FLC κ and λ assays in clinical samples determined in a single academic center. Methods: Serum FLCs were analyzed from 102 patients using the Freelite (Binding Site) and N Latex (Siemens) assays on the BN ProSpec System (Siemens). When available, data for protein electrophoresis, immunofixation, C-reactive protein, and estimated glomerular filtration rate (eGFR) were combined with FLC results to evaluate performance. Results: Method evaluation showed acceptable imprecision and inaccuracy measures of <4.4% and 12.9%, respectively. Poor agreement between the methods was observed, including constant and proportional bias and poor correlation (Kendall τ, 0.671–0.901). The N Latex assay was not affected by the renal impairment estimated by eGFR, unlike the FLC κ/λ ratio results by the Freelite assay. With the Freelite assay, 98% of putative controls without monoclonal gammopathy (n = 42) showed a κ/λ ratio that was above the median of the standard diagnostic range or renal diagnostic range. A shift toward higher κ/λ ratios was also observed when retrospective data between 2011 and 2017 were compared. Conclusions: Unlike the Freelite assay, κ/λ ratios analyzed with the N Latex assay were not affected by renal failure. Both methods showed acceptable performances using nephelometry, but they were poorly correlated. A shift toward κ/λ ratios might impair the specificity of borderline increased κ/λ results. This should be considered when interpreting FLC κ and λ results.